1991
DOI: 10.1073/pnas.88.17.7797
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase and neuronal NADPH diaphorase are identical in brain and peripheral tissues.

Abstract: NADPH diaphorase staining neurons, uniquely resistant to toxic insults and neurodegenerative disorders, have been colocalized with neurons in the brain and peripheral tissue containing nitric oxide synthase (EC 1.14.23.-), which generates nitric oxide (NO), a recently identified neuronal messenger molecule. In the corpus striatum and cerebral cortex, NO synthase immunoreactivity and NADPH diaphorase staining are colocalized in medium to large aspiny neurons. These same neurons colocalize with somatostatin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
793
1
12

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,536 publications
(844 citation statements)
references
References 27 publications
(29 reference statements)
38
793
1
12
Order By: Relevance
“…In agreement with others, we found that hyperosmotic stimulation of early and late adulthood rats triggered an activitydependent increase in NADPH-d staining density in the SON (Soinila et al, 1999;Yun et al, 2005). The increased NADPH-d staining is likely representative of neuronal NOS (nNOS) since NADPH-d has been shown to colocalize with nNOS (Dawson et al, 1991;Hope et al, 1991) but less reliably with endothelial NOS (eNOS) (Dinerman et al, 1994) and inducible NOS (iNOS) (Tracey et al, 1993). In support of this we show that stimulated NADPH-d staining is suppressed by in vitro treatment with the general NOS inhibitor, L-NNA, with highest affinity for nNOS (K i = 25 nM) and whose binding sites in the rat CNS correspond well with anti-NOS immunohistochemical staining (Kidd et al, 1995;Reif and McCreedy, 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with others, we found that hyperosmotic stimulation of early and late adulthood rats triggered an activitydependent increase in NADPH-d staining density in the SON (Soinila et al, 1999;Yun et al, 2005). The increased NADPH-d staining is likely representative of neuronal NOS (nNOS) since NADPH-d has been shown to colocalize with nNOS (Dawson et al, 1991;Hope et al, 1991) but less reliably with endothelial NOS (eNOS) (Dinerman et al, 1994) and inducible NOS (iNOS) (Tracey et al, 1993). In support of this we show that stimulated NADPH-d staining is suppressed by in vitro treatment with the general NOS inhibitor, L-NNA, with highest affinity for nNOS (K i = 25 nM) and whose binding sites in the rat CNS correspond well with anti-NOS immunohistochemical staining (Kidd et al, 1995;Reif and McCreedy, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…NADPH is a required cofactor for NOS enzyme activity (Dawson et al, 1991) and NOS has NADPH-d activity (Hope et al, 1991). An enhancement of NADPH-d staining in fixed sections coincides with a respective rise in the amount of NOS protein (Kishimoto et al, 1996) and NOS gene expression (Kadowaki et al, 1994); therefore, NAPDH-d staining can be used as an indicator of NOS activity in paraformaldehyde-fixed tissue (Matsumoto et al, 1993;Young et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme survives fixation, whereas other similar enzymes are inactivated (Hope et al, 1991;Dawson et al, 1991;Hiramatsu et al, 1999). Applying this method to whole embryos, we found that NOS is present in the developing NT and adjacent tissues at 8-to 12-somite stages (see Fig.…”
Section: Results and Discussion Nitric Oxide Synthase Is Present In Dmentioning
confidence: 89%
“…Improper regulation of these factors can lead to impaired cellular functioning, modified neurotransmitter action, amplified inflammation and neuronal damage. Various potential neurotoxins are generated and released during the inflammatory process including reactive oxygen species, tumor necrosis factor-α (TNF-α), arachidonic acid, platelet-activating factor (PAF), nitric oxide, quinolinic acid, and glutamate (20,30,(46)(47)(48)(49)(50)(51)(52).…”
Section: Macrophage Driven Pathogenesismentioning
confidence: 99%